2022
DOI: 10.55056/etq.32
|View full text |Cite
|
Sign up to set email alerts
|

The current level of competence of schoolteachers on how to use cloud technologies in the educational process during COVID-19

Abstract: During the period of total lockdown caused by COVID-19 pandemic, teachers had to move to distance learning to organize a continuous educational process, which is not possible without the active use of modern information and communication technologies, including cloud services. Because of this, at the beginning of the pandemic, Zhytomyr Polytechnic State University conducted several free distance online courses for teachers, which included studying the possibilities of using cloud technologies in teaching in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…Meanwhile, Calderón et al (2019) and Plak et al (2022), for example, found no significant correlation between these variables. The current finding that views of faculty online assessment and feedback were more effective in married pre-service teachers is consistent with Chibisa et al (2022) and with Yıldırım and Tekel (2023), who found that married pre-service teachers reported a positive impact of online assessment on their academic performance, crediting their stronger engagement in online education to the comfort of their home environment. Conversely, Nikoçeviq-Kurti (2023) found no significant effect of marital status on positive aspects of online teaching and quality of teaching activities.…”
Section: Research Questionsupporting
confidence: 90%
“…Meanwhile, Calderón et al (2019) and Plak et al (2022), for example, found no significant correlation between these variables. The current finding that views of faculty online assessment and feedback were more effective in married pre-service teachers is consistent with Chibisa et al (2022) and with Yıldırım and Tekel (2023), who found that married pre-service teachers reported a positive impact of online assessment on their academic performance, crediting their stronger engagement in online education to the comfort of their home environment. Conversely, Nikoçeviq-Kurti (2023) found no significant effect of marital status on positive aspects of online teaching and quality of teaching activities.…”
Section: Research Questionsupporting
confidence: 90%
“…Digitalization of education has become the subject of many scientific studies devoted to the theoretical and methodological foundations of distance education (Myroslav I. Zhaldak [8], Yukhum I. Mashbyts [9], Illia O. Teplytskyi [10], Svitlana V. Shokaliuk [11]); blended learning (Liudmyla I. Bilousova [12], Kateryna P. Osadcha [13], Iryna S. Mintii [14], Serhiy O. Semerikov [15], Yurii V. Tryus [16]); development of the informational and educational environment (Mariia A. Kislova [17], Kateryna I. Slovak [18], Liubov F. Panchenko [19], Kateryna V. Vlasenko [20], Olena O. Lavrentieva [21], Mariana M. Kovtoniuk [22], Tetiana A. Vakaliuk [23], Yuriy L. Kuchyn [24], Oleksandr Yu. Burov [25]); and information and communication competence of teachers in the conditions of a cloud-oriented educational environment (Kateryna V. Vlasenko [26], Iryna V. Lovianova [27], Tetiana A. Vakaliuk [28], Nataliia V. Morze [29], Mykhailo V. Moiseienko [30]); adaptive cloud-oriented system of training and professional development of teachers of secondary school (Hanna B. Varina [31], Yuliya H. Nosenko [32], Kateryna P. Osadcha [33]); determination of teachers readiness and need of digital tools and ICT during quarantine (Oksana V. Ovcharuk [34]); digital transformation of education (Tetiana V. Sych [7], Olga P. Pinchuk [35], Oksana V. Ovcharuk [36], Andrey V. Pikilnyak [37]).…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…-Examining the well-being of employees during remote work and the impact of stress on their mental health [130]. -Exploring the use of cloud technologies in education during the COVID-19 pandemic, potentially enhancing education and well-being [131]. -Enhancing physical education teachers' competency in health preservation, contributing to improved well-being [132].…”
Section: Icsf 2023 Program Committeementioning
confidence: 99%